Optimising the Role of the Financial Services Authority for a More Sustainable Business Ecosystem in Indonesia - Ulya Yasmine Prisandani (Universitas Airlangga, 2022)
This paper elaborates the role of the Indonesian Financial Services Authority in providing a legal framework, for public and financial services companies in particular, for achieving sustainability. It also provides a comparative analysis of sustainability regulations and functions undertaken by financial services authorities in other jurisdictions. This research takes a normative approach, combining an assessment of Indonesian laws and regulations related to business sustainability and a comparative approach; the latter provides insight into the comparable legal framework in the European Union and the United Kingdom. The Indonesian Financial Services Authority issued regulations on sustainable financing in 2017, and its sustainability roadmap was updated in 2021. Comparable provisions are found in the United Kingdom’s Financial Conduct Authority’s guiding principles on design, delivery, and disclosure of environmental, social and governance and sustainable investment funds, which acts as a supplement to the EU’s Sustainable Finance Disclosure Regulation. This paper hopes to contribute to the literature on business and human rights by providing an overview of the current role of the Indonesian Financial Services Authority in ensuring the sustainability of businesses under its auspices in comparison with similar agencies in the United Kingdom and European Union. Research on business and sustainability in Indonesia from a legal perspective is still rare, despite the rising urgency of the matter in developing business and human rights as well as climate change mitigation strategies.